Film Attack on Titan dalam Pandangan Filsafat Eksistensialisme Jean-Paul Sartre - Haqqi, Sabilal; Abbas, Mardhiah; Faza, Abrar M. Daud (AHKAM, 2024)
Jean-Paul Sartre is a famous figure in the fields of philoshophy and literature, considered one of the parents of contemporary existentialism. Existentialism is a philosophical school which argues that all phenomena originate from existence, or the existence of something. Existentialism is a protest against the concept of “logic” and “nature” which were emphasized in the enlightenment period (Enlightenment) in the eighteenth century. Sarte’s existentialist philosophical thought is La Liberte or human freedom. Humans are free, independent. Therefore, he must be free to determine and decide, he acts alone without other people around or with him. This research analyzes Jean-Paul Sartre's views on the theory of existentialism in the film Attack on Titan. This film is related to the theory of existentialism by Jean-Paul Sartre, a philosopher who developed the current of existentialism. By using the research method "library research" with a qualitative approach. The aim of this research is to describe the philosophical views of existentialism and analyze the extent to which the values and concepts in Jean-Paul Sartre's theory can be harmonized with the principles of Islamic teachings. In conclusion, it can be seen that the film "Attack on Titan" effectively reflects Sartre's thoughts about free human existence and responsibility for the world around him. Jean-Paul Sartre's existentialism, although emphasizing personal responsibility and individual freedom, was secular and perhaps not in harmony with religious principles, especially Islam. Some concepts of existentialism, such as the emphasis on absolute freedom, can conflict with the Islamic view which places obedience to Allah as the main principle.